PEMILIHAN SITUS MEDIA ONLINE TERHADAP KEBUTUHAN END USER DENGAN PENDEKATAN MULTI CRITERIA DECISION MAKING (MCDM) - Akmaludin, Akmaludin (Jurnal Pilar Nusa Mandiri, 2014)
Wireless Internet usage is now a major requirement virtual world, even the role of information and communication technology to support the advancement of the use of internet facilities. All forms of life in the media business online communication is needed at all because the information needs to be a necessity for business users and players. Lines of communication can be done in various ways, one of which can use online media, such as e-books, e-magazines, newspapers online through the websites of online media. There are so many online media sites which are known among the better-known as seconds, tempo, Republika. To analyze online media sites to the needs of the user takes an objective measurement methodology that can be known empirically. The methodology used using Multi-Criteria Decision Making approach (MCDM). In Analytic Hierarchical Process ( AHP ) to know a lot of approaches to decision making. MCDM approach of choice in this paper on the grounds will be applied using the Expert Choice. Advantages of this application are more precise analysis results used directly to prove the MCDM approach. The main criteria used include interfacing, simplicity, quality, satisfaction, and benefits, each criterion has sub- criteria as detailed analysis. The Acquisition of the analysis conducted on the three sites mentioned above with MCDM approach and a kind to using Expert Choice application by the end of the following synthesis Media such as, Republika online with a priority value of 0.476 , followed by the second and subsequent online media due to the sequential priority value is 0.293 and 0.231 . The results obtained have the same priority value analysis done with matrix algebra approach by mathematical concepts.